Transforming food waste into energy: A comprehensive review - Shama Kakkar; Nagaraju Dharavat; Suresh Kumar Sudabattula (Results in Engineering)
The proliferation of food waste has emerged as an escalating issue, with forecasts suggesting a persistent increase. Efficient waste management is essential in tackling environmental difficulties, providing a sustainable approach to alleviate these urgent problems. Fruit and vegetable waste (FVW) is notable among waste kinds for its abundant critical nutrients, dietary fibre, bioactive chemicals, and significant energy potential. Establishing an effective system for processing FVW can provide substantial advantages, especially in energy recovery and waste minimisation. The worldwide society is increasingly prioritising renewable energy sources to mitigate the environmental repercussions of fossil fuel consumption. Global initiatives are currently focused on utilising energy from FVW, along with the overarching objective of achieving international energy security. This article investigates the possibilities of power generation from many forms of food waste, analyses prevalent generating methods and their justifications, and addresses the legislation and regulations governing food waste management, as well as prospective pathways for sustainable energy solutions.